TINJAUAN YURIDIS PERLINDUNGAN HUKUM BAGI KONSUMEN DARI KLAUSULA EKSEMSI DALAM KONTRAK STANDAR PERJANJIAN SEWA BELI - Dias Pramiari, Putu Ayu; Tuni Cakabawa L., Putu (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 10, Oktober 2013)
The paper shall be titled "Judicial Review of Legal Protection For ConsumersFrom Exemption Clause In Standard Contract of Hire Purchase Agreements". Recently,many people do Hire-Purchase Agreements. Hire-Purchase Agreement is an agreementbetween the seller and the tenant, that the seller agrees to let the tenants use the goodswithin the specified time and pay a sum of money periodically. When it’s paid off, theownership of the goods will automatically move to the tenant. This agreement is part ofstandard contract that made by one hand, in this case is the seller, so the consumer onlyhave to choose to take it or leave it. But, realize it or not, the seller deliberately putexemption clause in the standard contract. It causes damages for consumers. Therefore,it is need to know the protection measures by consumer itself to prevent the damages.
Keywords: Consumer, Exemption Clause, Standard Contract, Rent-Purchase Agreement